Modeling particulate waste assimilation by blue mussels within the spatial constraints of a commercial fish farm: implications for multitrophic aquaculture - á Norði, Gunnvør; Lund, Ivar; Andreasen, Birgitta; Taylor, Daniel; Johannesen, Tróndur T.; Jacobsen, Bjartur; Hughes, Adam D. (Frontiers in Marine Science, 2023)
Commercial salmonid farming is typically performed in open-water net cages where interactions between the environment and production unit might be widespread and not easily predicted or controlled. Integrated Multitrophic Aquaculture (IMTA) has been suggested to mitigate some of the environmental impacts. Based on empirical data, the assimilation of particulate waste from a commercial fish farm was modelled by two approaches to salmon/blue mussel IMTA; a system with mussels at the surface next to the fish farm and an alternative setup with mussels submerged under the farm. According to the model, 15 % of the feed was defecated and assumed available to the mussels and the submerged mussel farm could assimilate 14.6 % of the feces. Sensitivity analysis showed that current speed, the mussel filtration rate and the proportion of the material that settles slowly had an impact on this assimilation estimate, which could be significantly higher. However, the model did not include assimilation limitations due to particle size, which may contribute significantly to the submerged farm. The mussel farm at the surface mainly received small slow settling particles, and according to the model, only 0.4 % of the fish farm waste was assimilated. The maximum obtainable assimilation was 5.5 %. The fraction of slowly settling waste had the most pronounced influence on waste assimilation in the mussel farm at the surface. This is also amongst the most uncertain parameters since the relative portion of different settling velocities of fish feces is highly variable and more information on the size distribution of waste is needed.